ANALISIS PENGARUH TOTAL QUALITY MANAGEMEMT TERHADAP KINERJA MANAJERIAL PADA PEMUDA BAKERY AND CAKE DI KOTA AMBON - Fransiska N. Ralahallo; Josia Pattipeiluhu (Soso-Q : Jurnal Manajemen, 2017)
This study aimed to examine the effect of the variable Total Quality Management (Customer focus, team work, continuous improvement systems and employee involvement and empowerment) to managerial performance. Samples used in this study were 38 respondents who are employees YOUTH Bakery and Cake. Model analysis used is multiple regression. Testing the quality of the data used is the validity and reliability testing. The classical assumption used is normality test, multicollinearity, and test heterokedastisitas. Testing the hypothesis is significant simultaneous test (test - F), partial significance test (t - test) and adjusted R-square. The results showed that TQM simultaneous effect on managerial performance and there is only one variable in the TQM partial effect of variable teamwork. Adjusted R-square value of 0, 156 showed that managerial performance can be explained by the focus on the customer, teamwork, berksinambungan system improvement, and employee engagement and empowerment. Keywords: Total quality managemet, Customer focus, team work, continuous improvement systems, involvement and empowerment of employees, managerial performance.